2019
DOI: 10.29313/mimbar.v35i1.4223
|View full text |Cite
|
Sign up to set email alerts
|

The Shifting of Halal Certification System in Indonesia: From Society-Centric To State-Centric

Abstract: The aim of this paper is to describe the shifting of halal certification system in Indonesia, which previously tended to be society-centric towards state-centric. The needs of domestic consumers for a legally strong halal assurance system and the spread of global halal trend encourage the birth of Law Number 33 of 2014. The law makes halal certification compulsory rather than voluntary, in which the control conducted by the arrangements of LPPOM MUI is shifted to the superintendence of the Ministry of Religion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 4 publications
0
23
0
6
Order By: Relevance
“…There were studies concerning the development of halal regulations (Akim et al, 2019;Asa, 2019), its implementation (Anwar, Fahrullah, & Ridlwan, 2018;Nafis, 2019;Othman, Shaarani, & Bahron, 2016;Zulkifli & Mochammad Sahid, 2018), and its organizations (Afroniyati, 2014;Faidah, 2017), as well as problems in certification (Prabowo, Rahman, Rahman, & Samah, 2015;Viverita & Kusumastuti, 2017). Except Afroniyati and Faidah's study, the studies have not revealed the inter-organizational relations after the enactment of the Act No.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There were studies concerning the development of halal regulations (Akim et al, 2019;Asa, 2019), its implementation (Anwar, Fahrullah, & Ridlwan, 2018;Nafis, 2019;Othman, Shaarani, & Bahron, 2016;Zulkifli & Mochammad Sahid, 2018), and its organizations (Afroniyati, 2014;Faidah, 2017), as well as problems in certification (Prabowo, Rahman, Rahman, & Samah, 2015;Viverita & Kusumastuti, 2017). Except Afroniyati and Faidah's study, the studies have not revealed the inter-organizational relations after the enactment of the Act No.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although searching for meaning is a subjective problem, seeing what is written and what is implied is interesting in the study of language, especially if it is related to the expression of the meaning of policy regulation. Many studies on halal policy in Indonesia have been carried out (Afroniyati, 2014;Akim, Konety, Purnama, & Korina, 2019;Asa, 2019), but there are still gaps in knowledge about the interpretation of policies issued and their implications for relations between organizations related to these policies. Linking to institutional theory, the current issues for institutional theorists are about institutional complexity and contradiction, as well as organizational responses to institutional pressures (Greenwood, Díaz, Li, & Lorente, 2010;Greenwood, Raynard, Kodeih, Micelotta, & Lounsbury, 2011;Pache & Santos, 2010;Reay & Hinings, 2009;Thomann, Lieberherr, & Ingold, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In Indonesia, the history of halal certification has taken a relatively linear route, consisting of two major phases, namely before and after the promulgation of Law No 33 of 2014 about Halal Product Assurance (UUJPH, Undang-Undang Jaminan Produk Halal) [17]. Before UUPJH came into existence, MUI was the sole institution responsible for halal certification in Indonesia [9].…”
Section: History Of Halal Certification In Indonesia and Malaysiamentioning
confidence: 99%
“…After the advent of UUPJH, halal certification in Indonesia became mandatory. In fact, when it is fully implemented, Indonesia would be the first country in the world to require halal certification for every product in its market [17].…”
Section: Halal Certification Procedures In Indonesia and Malaysiamentioning
confidence: 99%
See 1 more Smart Citation